Quality of orthodontic care in an academic setting in the Middle East - Kabir Syed Gyasudeen; Abdelrahman Arafat Yousef; Raed Alrubaiaan; Osama Khader; Ahmed Ghoneima; Sabarinath Prasad (Scientific Reports)
Abstract Assessment of the quality of orthodontic care in a UAE-based orthodontic postgraduate training institution was conducted using multiple indices, including the Peer Assessment Rating (PAR), American Board of Orthodontics Objective Grading System (ABO-OGS), and Index of Complexity Outcome and Need (ICON). Retrospective evaluation of pre- and post-treatment records of patients (n = 201) treated with fixed orthodontic appliances was performed by two examiners Statistical analysis assessed the influence of gender, type of malocclusion, need for extraction, missed appointments and number of treating residents on treatment duration. The average numerical reduction of the PAR and ICON scores at the start and end of the treatment were 17.2 and 30.3, respectively, while the ABO-OGS post-treatment score was 14.8. The average PAR score reduction (84.5%) showed that the majority of the patients showed significant improvement at the end of treatment. Treatment duration correlated positively with ICON case complexity (p = 0.003), number of treating residents (r = 0.572, p < 0.001), and missed appointments (r = 0.671, p < 0.001) and negatively with age at treatment initiation (r = − 0.165, p = 0.019). The study findings indicated favorable outcomes for the quality of orthodontic care delivered by residents in a postgraduate training institution, though there were areas needing improvement. Optimizing the number of treating residents and minimizing missed appointments could further enhance clinical care.